ANALISIS KEKUATAN IMPACT DAN MODEL PERPATAHAN KOMPOSIT POLYESTER BERPENGUAT SERAT ALAM IJUK - Kadek Rihendra Dantes; Edi Elisa; I Made Pasek Budi Susila (Jurnal Rekayasa Mesin, 2023)
The objective of this study is to find significant differences in impact forces between continuous, discontinuous, and woven fiber type of polyester composites with natural palm fibers and to find out the description of the microfracture structure. This study used experimental methods with independent and dependent variables. The independent variables are continuous, discontinuous, and woven fiber type. Then, the dependent variable was impact forces. Based on the results of tests, show that results from the average score at continuous fiber type = 1.082.88 J/m2, discontinuous = 794.67 J/m2 and woven = 1.427.06 J/m2. The conclusion of this study is that between various fiber orientations was a significant difference in impact forces. The type of woven fibers has a higher value compared to the type of continuous and discontinuous fibers. Discontinuous fiber type has a lower score than continuous fiber type. The fracture model of polyester composite with natural palm fibers showed the mechanism of brittle fracture (brittle) in all test specimens. However, in specimens with the type of continuous fibers and woven, the fracture conditions indicate a brush fracture mechanism.